Building A Synergy Between The Halal Industry And The Green Industry In The Maqasid Syari'ah Review As The Basis Of Islamic Economics - Achmad Fageh (Journal of Islamic Economic Laws, 2022)
Industrial estates are usually reflected in the existence of a sure standardization. The halal industry gave birth to "Halal supply chain management," starting with halal standards procurement, manufacturing, distribution, and logistics. The green industrial area was first born by prioritizing environmental sustainability, namely efficiency in using renewable energy, environmentally friendly substitute raw materials, and waste treatment. So far, there has not been continuity seen in the Policy, so the concept of Maqasid Sharia as the basis of Islamic economics, which prioritizes "halalan thoyyiban" or halal and suitable, has not been used as a foundation to synergize the goodness of each industrial area so far. This research offers a concept of halal and environmental sustainability, which is reflected in the following industry supply chains. (1). Procurement of goods in a halal manner with environmentally friendly product raw materials criteria. (2). Manufacturing process by prioritizing the use of renewable energy. (3). Processing of waste products (gas, liquid and solid) to not damage the surrounding environment. (4). Halal Logistics and Distribution. So that what is contained in Maqashid Syariah can be implemented in this new concept